1997
DOI: 10.1093/emboj/16.13.4126
|View full text |Cite
|
Sign up to set email alerts
|

Release factor RF3 in E.coli accelerates the dissociation of release factors RF1 and RF2 from the ribosome in a GTP-dependent manner

Abstract: The first attempt to explain the role of RF3 in translation 2 Corresponding author termination proposed a dual function, first to stimulate the email: ehrenberg@xray.bmc.vv.se binding of RF1 and RF2 (RF1/2) to the ribosome, and secondly to catalyse the dissociation of the factors from Ribosomes complexed with synthetic mRNA and pepthe ribosome after hydrolysis of peptidyl-tRNA in a tidyl-tRNA, ready for peptide release, were purified by reaction dependent on guanine nucleotide, thereby stimugel filtration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
254
1
3

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 265 publications
(266 citation statements)
references
References 40 publications
8
254
1
3
Order By: Relevance
“…RF2 recognizes UAA and UGA with about equal efficiency (14), so it might have been expected that the efficiency with which the factor reads the sense codons AAA and AGA or GAA and GGA would be similar. In contrast, we find that RF2 becomes much more error-prone when G rather than A is present in the second position, although both dinucleotides AA and AG are part of the normal stop codons of the factor (Table 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RF2 recognizes UAA and UGA with about equal efficiency (14), so it might have been expected that the efficiency with which the factor reads the sense codons AAA and AGA or GAA and GGA would be similar. In contrast, we find that RF2 becomes much more error-prone when G rather than A is present in the second position, although both dinucleotides AA and AG are part of the normal stop codons of the factor (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…RF1 normally terminates at UAA and UAG and RF2 at UAA and UGA (10). The dissociation of both factors from the ribosome after hydrolysis of the ester bond in peptidyl-tRNA connecting peptide chain with tRNA is accelerated by a third RF, the G-protein RF3 (11)(12)(13), and this seems so far to be its only function (14). The three stop codons together have about 20 sense codons as nearest neighbors (Tables 1 and 2), and hot spots for false stops are likely to be found within this set of sense triplets.…”
mentioning
confidence: 99%
“…Macrolides that do not reach the PT center allow formation of longer peptides, and erythromycin, which belongs to this sub-class, was chosen as the other model compound. The mechanisms of action of josamycin and erythromycin were studied in a cellfree translation system, reconstituted from pure E. coli components (7,17).…”
Section: Discussionmentioning
confidence: 99%
“…In this study we have clarified some of these issues for the macrolides erythromycin and josamycin by studying their kinetic properties in a cell-free system for protein synthesis with Escherichia coli components of high purity (7,17).…”
mentioning
confidence: 99%
“…Ehrenberg and his co-workers have reported that Escherichia coli RF3 accelerates the dissociation of the release factors RF1 and RF2 from the ribosome in a GTP-dependent manner and that fast recycling of ribosomes requires both RF3 and RRF [6,7]. Grentzmann et al [8] have observed similar results and found that RF3 can substitute for EF-G in RRFdependent ribosome recycling reactions in vitro.…”
Section: Introductionmentioning
confidence: 87%